Improved In Vitro Maturation of Goat Oocytes using Cysteamine and Epidermal Growth Factor-Enriched Media - Gond, Malasri; Gangaram Bijurkar, Rajeshwar; Kishanrao Tandle, Manik; Doddagoudar, Venkanagouda; Kulkarni, Shrikant; Rathod, Shesharao (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The current study was performed to see the effect of cysteamine and epidermal growth factor (EGF) on in vitro maturation of goat  oocytes (n=8516). The four maturation media used in the study were: Control (TCM-199 + FSH 1 µg/mL + 20 IU/mL hCG + 1 μg/mL  Estradiol + Gentamicin 50 μg/mL + 10% EGS); Group I (Control + 100 µM/mL Cysteamine); Group II (Control + 20 ng/mL EGF) and Group  III (Control + 100 µM/mL Cysteamine and 20 ng/mL EGF), involving 1591, 1252, 1242, and 1214 oocytes, respectively, for 50, 33, 31,  and 30 trials. Later the oocytes were incubated in CO2 incubator for 27 h at 38.5°C, 5% CO₂, and 90-95% relative humidity. The in vitro maturation of goat oocytes, assessed based on cumulus expansion (77.02±2.24 to 77.56±1.57 vs 52.63±1.84%) and first polar body  extrusion (55.01±3.00 to 64.11 ±1.93 vs 31.64±2.68%) was significantly higher (p≤0.05) in Group I, II and III compared to Control group.  In summary, the addition of cysteamine and epidermal growth factor alone or in combination in the maturation media had a beneficial  effect on maturation rate in goat oocytes.
Keywords: Cysteamine; Epidermal growth factor; In vitro maturation; Goat